TECHNOLOGIES FOR DEVELOPING CLINICAL SKILLS IN MEDICAL EDUCATION: OSCE, SIMULATION CENTERS, CLINICAL SCENARIOS, AND CHECKLISTS. (Multidisciplinary Journal of Science and Technology, 2026)
Background: Contemporary medical education demands competency-based approaches that ensure verifiable clinical skills in graduates. The integration of structured assessment tools and simulation-based learning has become a cornerstone of high-quality medical pedagogy globally. Objective: This study evaluates the pedagogical effectiveness of OSCE, simulation centers, clinical scenarios, and standardized checklists in undergraduate medical training at Tashkent State Medical University. Methods: A mixed-methods study involved 246 fourth- and fifth-year students divided into an intervention group (IG, n=123) and a control group (CG, n=123) over two academic years (2022–2024). OSCE scores, Clinical Confidence Scale ratings, procedural accuracy, and inter-rater reliability were measured. Results: IG students achieved significantly higher post-intervention OSCE scores (81.7 ± 6.2 vs. 68.4 ± 8.1; p